PELAYANAN KESEHATAN BERDASARKAN INDEKS KEPUASAN MASYARAKAT DI PUSKESMAS TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - jurnalmap map; Suardi ÔÇÄ; Indra Prasetyo (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to determine health services based on the community satisfaction index at the Tembilahan Hulu Community Health Center, Indragiri Hilir Regency. This research is a type of descriptive study using analysis of the Community Satisfaction Index with data results in the form of numbers. The results showed that the value of the Community Satisfaction Index (IKM) for services at the Tembilahan Hulu Puskesmas was in the good service quality category. The 14 indicators of the Community Satisfaction Index are as follows: (1) service procedures in the good category; (2) service requirements are in good category; (3) clarity of service personnel in either category; (4) discipline of service officers in good category; (5) service officer responsibilities are in the good category; (6) the ability of service personnel in the good category; (7) the speed of service in the poor category; (8) justice gets services in the good category; (9) courtesy and friendliness of service personnel in the good category; (10) the fairness of service costs in the good category; (11) certainty the cost of services in the good category; (12) certainty of the service schedule in the good category; (13) environmental comfort in both categories; and (14) service security in the good category.